Wood decomposers on six community timber species in two different locations - MARLINA WIDYA NURHADI; ARINANA ARINANA; ANINDYA INTAN RAHMAWATI; ELIS NINA HERLIYANA; RIKI ANDIKA; SETIAWAN KHOIRUL HIMMI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nurhadi MW, Arinana A, Rahmawati AI, Herliyana EN, Andika R, Himmi SK. 2023. Wood decomposers on six community timber species in two different locations. Biodiversitas 24: 6629-6640. Wood has a close relationship with termites and fungi as decomposers. Decomposers are important as dead organic matter is broken down into elements and returned to the soil. This study aims to analyze the amount of wood attacked by termites and fungi on six types of community timber during six months of testing at two different locations, analyze the degree of damage, and identify the species of termites and fungi that attack them. The research was conducted in two locations: the Arboretum of the Faculty of Forestry and Environment of IPB and a residential area in Bogor Asri, Cibinong Sub-district, Bogor District. The wood tested were Acacia mangium, Falcataria moluccana, Anthocephalus cadamba, Maesopsis eminii, Pinus merkusii, and Hevea brasiliensis. Tests were conducted based on ASTM D 1758-06. Infested wood increased with the time tested, and infestation was higher in the arboretum (75%) than in the residential area (39.4%). The highest level of wood damage in the arboretum was Hevea brasiliensis (35.4 g); in residential, it was Pinus merkusii (18.9 g). The subterranean termite types found during the six months of testing are Macrotermes sp., Microtermes sp., Schedorhinotermes sp., and Odontotermes sp. The weathering fungi types found during the six months of testing were  Aspergillus sp., Mucor sp., Trichoderma sp., Gliocladium sp., Mycelia sterilia, and red fungus. Soil type, moisture, and ambient temperature also strongly favored the development of decomposer life found in the two research sites.